Identification Of The Variables Influencing Employee Performance - April Widianto, Mochamad Rizky; Maulana, Aldi Suharsono; Rangga, Rangga (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The goal of this study is to determine whether or not employees' performance at PDAM Tirta Kamuning Kuningan is impacted by work communication and discipline. Personnel from PDAM TIrta Kamuning Kuningan participated in the study. The sample strategy employed in this investigation is random sampling, which is applied throughout. The sample size for the study consisted of 65 respondents. Although this study uses multiple linear regression analysis, data collection is done using questionnaires. The results of the study show that work communication and work discipline both significantly and favorably affect performance, as indicated by the tcount > ttable values of 7.359 > 1.669 and 14.689 > 1.669, respectively. Furthermore, as the tcalculate > Ftable values of 137.643 > 3.14 show, the factors of work communication and work discipline also have positive and substantial effects on kinerjs. Every single result, whether in full or in part, has a sig value that is less than 0.05 or 0.000 < 0.05. Communication within the organization significantly affects how well employees perform their duties. The level of work discipline among employees is a critical factor influencing their performance. Both communication and work discipline together have a significant combined effect on employee performance